Together Apart: Bitches Set Traps During Lockdown - McNutt, Elizabeth (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
In this piece, Elizabeth McNutt discusses the creative responses of the Texas-based group Bitches Set Traps to the pandemic. Building on the legacy of the pioneering Feminist Improvising Group (which similarly blended the political, personal, and musical), Bitches Set Traps combines musical improvisation with theatrical and comedic elements to challenge gender stereotypes and to comment on current events. In the early months of the pandemic, the group staged a series of collaborative performances over Zoom, addressing pandemic-related themes including the household division of labor, the importance of self-care, beauty standards during quarantine, and social distancing.